Ponatinib/blinatumomab for relapsed Philadelphia chromosome-positive leukemia as a bridge to allogeneic transplantation - Yasutaka Sadaga; Daisuke Watanabe; Yuho Najima; Daichi Sadato; Chizuko Hirama; Kana Kato; Kaori Kondo; Chika Kato; Satoshi Sakai; Yasuhiro Kambara; Masashi Shimabukuro; Atsushi Jinguji; et al. (Hematology, 2025)
We report three cases of ponatinib/blinatumomab (Pona/BLIN) combination therapy as a bridge to allogeneic hematopoietic cell transplantation (allo-HCT) in patients with relapsed/refractory Philadelphia chromosome-positive acute lymphoblastic leukemia (r/r-Ph + ALL) or lymphoid chronic myeloid leukemia blast crisis (CML-BC). Case 1: A 60-year-old man with Ph + ALL achieved molecular complete remission (mCR) with Pona/BLIN after relapse following initial dasatinib-based treatment and subsequently underwent allo-HCT. Case 2: A 39-year-old man with Ph + ALL achieved hematological CR (hCR) with one cycle of inotuzumab ozogamicin and mCR with Pona/BLIN after post-transplant relapse but developed extramedullary relapse with BCR::ABL-negative clone and underwent a second allo-HCT in non-remission. He subsequently developed hematological relapse. Case 3: A 57-year-old woman initially diagnosed with myeloid CML-BC achieved mCR with chemotherapy regimens and dasatinib maintenance but relapsed as lymphoid CML-BC. She achieved hCR with Pona/BLIN and proceeded to allo-HCT. None of the cases developed grade 3 or higher adverse events during treatment. These cases suggest that Pona/BLIN combination therapy is safe and effective as a bridging strategy to allo-HCT, but extramedullary relapse caused by BCR::ABL-negative blasts can occur.